Religiosity and Islamic Financial Literacy in Gen-Z’s Islamic Bank Saving - Taufiqurrahman; Manggala Putri, Syah Amelia (LPPM Universitas Sangga Buana, 2025)
The research aims to determine the influence of religiosity and Sharia financial literacy on the interest of Gen Z students of the University of Muhammadiyah Yogyakarta in saving in Sharia banks. The population of this study were students at the University of Muhammadiyah Yogyakarta at Strata 1 level who belong to the Generation Z or Gen Z category, were Muslim and had not saved in a Sharia bank. The research method used quantitative methods. Data analysis was carried out using SPSS version 24 software tools. The results obtained in this study showed that religiosity had a positive and significant effect on Gen Z's interest in saving in Sharia banks whereas Sharia financial literacy had a positive and significant effect on Gen Z's interest in saving in Sharia banks. Further, religiosity and Sharia financial literacy simultaneously influence Gen Z's interest in saving in Sharia banks.